2018
DOI: 10.18535/ijsrm/v6i6.el06
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Self Efficacy, Job Satisfaction and Organizational Commitment Toward Organizational Citizenship Behavior (Ocb) of Teachers Of Private Vocational Schools in South Jakarta

Abstract: The objective of this research was to determine the direct influence of self efficacy, job satisfaction, organizational commitment and organizational citizenship behavior (OCB) of Vocational High Schools Teachers of South Jakarta. The research method using survey with correlation approach, in this study sampled as many as 172 teachers and selected based on a simple random technique (Simple Random Sampling). The research was done in State Vocational High School in the South of Jakarta. Based on the description … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 1 publication
0
2
0
1
Order By: Relevance
“…Previous research has shown a positive relationship between organizational commitment and organizational citizenship behavior (Allen et al, 2011;Gati et al, 2018;Lailatur Rizki et al, 2019;Nurjanah et al, 2020). Another finding discovers that there is a strong and positive relationship between these two variables and statistically significant in both public and private institutions (Grego-Planer, 2019).…”
Section: H1: Job Satisfaction Affects Organizational Citizenship Behaviormentioning
confidence: 88%
“…Previous research has shown a positive relationship between organizational commitment and organizational citizenship behavior (Allen et al, 2011;Gati et al, 2018;Lailatur Rizki et al, 2019;Nurjanah et al, 2020). Another finding discovers that there is a strong and positive relationship between these two variables and statistically significant in both public and private institutions (Grego-Planer, 2019).…”
Section: H1: Job Satisfaction Affects Organizational Citizenship Behaviormentioning
confidence: 88%
“…People with high self-efficacy are more involved, responsible, interested in, and satisfied with the job which propagates a high level of confidence in one's abilities. This result was supported by Dewi & Sudibya (2016), Mansor et al (2013), Anfajaya & Rahayu (2020), Ullah, Raza, Ali, Amjad, & Jadoon (2021), Rahman, Wan Sulaiman, Nasir, & Omar (2014), Makruf & Surakarta (2021), Kusumaninggati, Mukhtar, & Sujanto (2018), Na-Nan, Kanthong, & Joungtrakul (2021), and Pratiwi & Nawangsari (2021), which found that self-efficacy influences OCB positively.…”
Section: Path Analysis Resultsmentioning
confidence: 63%
“…Um elevado sentimento de eficácia está relacionado com uma melhor saúde geral, uma maior realização pessoal e uma melhor integração social (Bandura, 1977;Lubbers, Loughlin, & Zweig, 2005;Scholz, Doña, Sud, & Schwarzer, 2002;Schwarzer, 1992), com um melhor desempenho profissional (Barros & Batista-Dos-Santos, 2010;Gist, 1987;Latham & Pinder, 2005;Lubbers et al, 2005;Rhee, Hur & Kim, 2017;Stajkovic & Luthans, 1998), maior satisfação (Canrinus, Helms-Lorenz, Beijaard, Buitink, & Hofman, 2012;Caprara, Barbaranelli, Steca, & Malone, 2006;Judge, Bono, Erez, & Locke, 2005;Lee & Oh, 2015;Perdue, Reardon, & Peterson, 2007;Reizer & Hetssroni, 2015), uma motivação superior (Chen, Gully, Whiteman, & Kilcullen, 2000;Ciani, Summers, & Easter, 2008;Lloyd, Bond, & Flaxman, 2017;Pajares, 1997;Salas & Cannon-Bowers, 2001;Schepers et al, 2005), com a diminuição do burnout (Fida, Laschinger, & Leiter, 2016;Smeds et al, 2019), maior engajamento (Perera, Granziera, & Mcllveen, 2018), maior comprometimento organizacional (Bzuneck & Guimarães, 2003;Kusumaninggati, Mukhtar, & Sujanto, 2018;Lee & Kim, 2019;Tsai, Tsai, & Wang, 2011;Yousaf & Sanders, 2012) e ocupacional (Chan, Lau, Nie, Lim, & Hogan, 2008;Rots, Aelterman, Vlerick, & Vermeulen, 2007). Assim, é essencial haver instrumentos capazes de mensurar bem a autoeficáci...…”
unclassified